Global Olympics : historical and sociological studies of the modern games - Young, Kevin, 1959-; Wamsley, Kevin B. (Research in the sociology of sport., 2005)
The Olympic Games have become a subject of major importance to students, academics, sports bodies, politicians, urban planners, and the public at large. The Olympic Rings are among the most recognised symbols in the world, and there are few other cultural phenomena that attract such a significant following in the popular media or such widespread support among the nations of the world. "Global Olympics: Historical and Sociological Studies of the Modern Games" draws together some of the world's leading scholars on critical issues emerging from ancient Olympic contests and over one hundred years.